Anisotropic thermal behavior of extrusion‐based large scale additively manufactured carbon‐fiber reinforced thermoplastic structures. Issue 6 (7th May 2022) - Hassen, Ahmed Arabi; Dinwiddie, Ralph B.; Kim, Seokpum; Tekinap, Halil Levent; Kumar, Vipin; Lindahl, John; Yeole, Pritesh; Duty, Chad; Vaidya, Uday; Wang, Hsin; Kunc, Vlastimil
Abstract: Large format additive manufacturing (AM) enables rapid manufacturing of large parts and structures with minimum waste in material and energy. Extrusion‐based AM deposition processes provide parts with highly anisotropic thermal properties, which are not typically reflected in textbook values for these materials. In order to develop accurate models that describe the directionally dependent thermal behavior of these materials in processing and service, accurate measurements of specific heat capacity and thermal conductivity are required. This work characterizes, documents, and analyzes the effect of the anisotropic nature of the extrusion‐based deposition process on the specific heat capacity and thermal conductivity of the resulting AM products. All measurements were made over a temperature range of 20–180°C using the transient plane source technique, also referred to as the hot disk technique. Three of the most commonly used large format AM feedstock materials that utilize carbon fiber reinforcement were examined in this work: acrylonitrile butadiene styrene, polyphenylene sulfide and polyphenylsulfone. These findings can serve as a thermal design/process guideline for future large format AM applications.